Educação e humanidades digitais: aprendizagens, tecnologias e cibercultura - Sara Dias-Trindade (Investigação, 2019)
In recent years, the relationship with knowledge has undergone profound changes due to the expansion of digital technologies and interactive communication networks. Most people have experienced intense use of these technologies, which has directly affected their mental and social structures. The cognitive abilities of the subjects, in these digital grafocentric societies, require new and differentiated teaching-learning processes. Such clarity then requires different perspectives in analyzing the educational world, which is quite different - in the face of new audiences, new needs and new possibilities. Being and emerging and embryonic theme, there are still many gaps in this area's scientific literature, lacking new reflections and studies. Thus, the present work seeks to contribute to discussions of specific and necessary themes for this new vision of education, which aims at developing in its students varied interdisciplinary skills, adequate to the demands of the present millennium. This book aims to meet the interests of those who think or do quality education, exploiting the potential of emerging technologies.